Stargardt Disease Unmasked During Primigravida Pregnancy: A Case Report on Diagnosis and Low Vision Management - Ramzi Amin; Ginda Chitra (HM Publisher, 2024)
Stargardt disease (STGD1), the most prevalent inherited macular dystrophy in juveniles and young adults, typically results from biallelic mutations in the ABCA4 gene. It leads to progressive central vision loss due to lipofuscin accumulation in the retinal pigment epithelium (RPE) and subsequent photoreceptor degeneration. While onset often occurs in the first two decades, presentation can vary. Managing STGD1 involves optimizing remaining vision through low vision rehabilitation and addressing the psychosocial impact, particularly crucial during significant life events like pregnancy. We report the case of a 23-year-old Indonesian female, primigravida at 35 weeks of gestation, referred from obstetrics for evaluation of a longstanding visual impairment before delivery planning. She reported progressive bilateral blurred vision since age 7, significantly worsening over the past three years, accompanied by photophobia and difficulty reading, requiring close proximity to text. Her younger sibling also had similar visual complaints. Best-corrected visual acuity was 1/60 OD and 2/60 OS, unamenable to refractive correction. Fundus examination revealed bilateral macular atrophy with a